KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SMP NEGERI 1 MOJOLABAN TAHUN PELAJARAN 2014/2015 - Khoiriyah, Nor; Sujadi, Imam; Subanti, Sri (Journal of Mathematics and Mathematics Education, 2016)
Abstract. The purpose of this research was to describe the ability of studentâs mathematical communication who had low, medium, and high early mathematics ability in class VII SMP Negeri 1 Mojolaban on aspect grammatical, sociolinguistic, strategic, and discourse competence in solving mathematics problem. This research was a qualitative research. The subjects in this research were seven students of class VIIE SMP Negeri 1 Mojolaban, which consisted of three students who had low early mathematical ability, two students who had medium early mathematics ability, and two students who hadÂ  high early mathematical ability.The subjects in this research were taken by using the purposive sampling technique. The main instrument used in this research to collect the data was the researcher and the other instrument were a task that contains of test question and interview guide instrument. Data analysis technique were conducted by data reduction, data presentation and conclusion. The validity of the data was conducted by using time triangulation that compared the data of the first task based interviews with the data of the second task based interviews. The equal valid data of mathematical communication ability on aspect grammatical, sociolinguistic, strategic, and discourse competence was made the main finding, whereas the different of valid data was made other finding of the research. The result of this research are the students who had low, medium, and high early mathematics abilities were have imperfect mathematical communication on grammatical, sociolinguistic, strategic, and discourse competence. The imperfection that appearÂ  on each competence caused by some indicators that not fulfilled completely.Keywords: Mathematical communication, grammatical competence, discourse competence